Cosmic Mind?. Issue 1 (2nd January 2016) - Kauffman, Stuart
ABSTRACT: This article explores the remote scientific possibility of something like "cosmic mind" or "cosmic minds." Descartes proposed his famous dualism, res cogitans (mental reality) plus res extensa (physical reality). With Isaac Newton and classical physics, res extensa won in Western science and with it, we lost our minds; we lost our subjective pole. Quantum mechanics has seemed to many, since its formulation in the Schrödinger equation in 1926, to hint beyond physics to a role for the human conscious observer in quantum measurement. At least two interpretations of quantum mechanics, or its extension—the latter by Penrose and Hameroff, and the former by myself—suggest a new panpsychism where conscious awareness and possibly free will occur at quantum measurements anywhere in the universe. If so, then we live in a vastly participatory universe. More: entangled quantum variables may conceivably share some form of consciousness and free will, whether embodied in us, or living forms elsewhere in the universe, or disembodied; hence, something like cosmic mind or minds are not ruled out. If true, life anywhere in the universe will have evolved with mind and free will. Souls are not impossible.